Two new species of Fernandezina Birabén, 1951 (Araneae, Palpimanidae) from cave and epigean habitats in Brazil - Carvalho, Leonardo S.; Braga-Pereira, Gracielle F.; Santos, Adalberto J. (Zootaxa, 2024)
The South American palpimanid genus Fernandezina Birabén currently comprises 15 described species, all known from epigean environments. Representatives of Fernandezina are easily recognized by the unexpanded femora I in both sexes and by the dorsally extended opisthosomal scutum in males. Herein, F. fernandoi sp. nov. is described based on males and females from hypogean environments and F. angeloi sp. nov. is described based on a single male from a nearby epigean environment, both in Brazil. Additionally, we provide an identification key for the species of the genus.